Quality of life in South African Black women with alopecia: a pilot study. (6th November 2015) - Dlova, Ncoza C.; Fabbrocini, Gabriella; Lauro, Carlo; Spano, Maria; Tosti, Antonella; Hift, Richard H.
Abstract: Background: Alopecia has been shown to have a significant impact on quality of life (QoL), particularly in women. However, there are no data for African populations. This study was conducted to pilot an original questionnaire and a model‐based methodology to measure QoL and its determinants in a sample of South African Black women of African ancestry with alopecia. Methods: Fifty participants aged 21–79 years were randomly chosen from patients presenting to dermatologists with alopecia. We used an original questionnaire consisting of 24 items grouped into those assessing the respective impacts of subjective symptoms, objective signs, and relationship issues, measured on a four‐level scale. These were then combined using component‐based structural equation modeling to return a QoL index (QLI) and to rank the factors contributing to this. Results: On a scale ranging from 0 (high QoL) to 100 (severely decreased QoL), we found a mean QLI of 67.7. The negative impact of alopecia on QoL was higher in younger patients than older patients. The factors with the highest impact were those relating to the subjective experience of alopecia and self‐image (56.3%), followed by those relevant to relationships and interaction with other people (34.8%). The presence of objective symptoms and signs such as pruritus was of minor importance (8.9%). Conclusions: Although not a life‐threatening condition, alopecia may seriously impair QoL, particularly by inducing anxiety and reducing self‐esteem among African women. Healthcare practitioners should be mindful of this and intervene appropriately to mitigate these effects.